Journey through Data: Exploring Wellness Tourism through Bibliometric Analysis with Dimensions.ai Database - Bhatia, Arun; Sharma, Divyam; Kumar, Saurabh; Kumar, Umesh (Turizam, 2024)
Overarching the benefits of tourism a niche kind of tourism motivates people around the world to travel for wellness overcoming level of stress, enhance a sense of joy, harmonised body, mind, and spirit last but not the least gratifying customer experiences boosting an individual well-being has been highlighted as wellness tourism. Wellness Tourism is often erroneously conflated in the literature with medical tourism, despite constituting an entirely distinct segment of health tourism. Furthermore, very few thorough reviews have been done up to the current times to evaluate the after effects of COVID-19 on wellness stream of research and emergence of its prominence in wellness tourism studies. Fulfilling the gap bibliometric analysis technique using dimension.ai is used to evaluate the article authorship, publication trend, co-authorship with synthesis of total article with a total of 1005 pertinent publications written in English-language using mapping technique of VOSviewer programme, relational approaches and evaluation methodologies based on productivity and impact indicators. Proposals and recommendations for future research are highlighted to explore the future dimension of the research in wellness tourism field. KeywordsWellness Tourism, Health Tourism, Medical Tourism, Dimensions.ai, Bibliometric Analysis, COVID-19